Parallel programming and performance predictability with Orléans Skeleton Library - Javed, Noman; Loulergue, Frederic (2011 International Conference on High Performance Computing and Simulation, 2011)
Orleans Skeleton Library (OSL) is a library of parallel algorithmic skeletons in C++ on top of MPL It provides a structured approach towards parallel programming. Skeletons in OSL are based over the bulk synchronous parallelism model. Applications can be developed using different combinations and compositions of the skeletons. This paper illustrates the expressivity and performance predictability of OSL with two applications: a two dimensional heat diffusion simulation, and an exact N-body simulation. Experiments using these applications are performed on parallel machines.